Lycopsida from the lower Westphalian (Middle Pennsylvanian) of the Maritime Provinces, Canada - Álvarez-Vázquez, Carmen; Wagner, Robert H. (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 2014)
A taxonomic revision of lycopsids is presented as part of a reassesment of lower to middle Westphalian adpression floras from the Maritime Provinces of Canada. Being elements of the swamp flora their record reflects sedimentary bias. Systematic collecting from the “Fern Ledges” at Saint John (New Brunswick) has yielded only a few lycopsid remains as a result of the allochthonous facies. Most records (mainly by W.A. Bell in the twentieth century) correspond to sporadic collecting by Geological Survey of Canada (GSC) personnel. Their specimens are kept in GSC Ottawa. Additional remains are in museums at Montréal (Quebec), Joggins (Nova Scotia) and Saint John (New Brunswick). We introduce a new species (Lepidodendron bellii), and reinstate another (Diaphorodendron decurtatum) described by Dawson in the 19th century. Altogether, 26 taxa are described, including stem and branch remains as well as roots, leaves, strobili and sporophylls. Three specimens are illustrated from localities outside Canada so as to clarify specific characters. A copy of Lindley and Hutton’s illustration of the type of Lepidodendron dilatatum (here recorded as Bergeria dilatata) is figured in the context of a redefinition of the genus Bergeria for stem remains with false leaf scars. Problems surrounding the morphological interpretation of arborescent lycopsids of Pennsylvanian age are discussed, and the stratigraphic and paleogeographic distribution are recorded for the different taxa. The identity of the Pennsylvanian flora of the Canadian Maritimes with that of the British Isles and western Europe in general is emphasized by the synonymies discussed. Paleogeographic proximity and a similar paleolatitude justify the identity of floras.